Advances in the biotechnology of hydrogen production with the microalga Chlamydomonas reinhardtii. (22nd April 2014) - Torzillo, Giuseppe; Scoma, Alberto; Faraloni, Cecilia; Giannelli, Luca
Abstract: Biological hydrogen production is being evaluated for use as a fuel, since it is a promising substitute for carbonaceous fuels owing to its high conversion efficiency and high specific energy content. The basic advantages of biological hydrogen production over other "green" energy sources are that it does not compete for agricultural land use, and it does not pollute, as water is the only by-product of the combustion. These characteristics make hydrogen a suitable fuel for the future. Among several biotechnological approaches, photobiological hydrogen production carried out by green microalgae has been intensively investigated in recent years. A select group of photosynthetic organisms has evolved the ability to harness light energy to drive hydrogen gas production from water. Of these, the microalga Chlamydomonas reinhardtii is considered one of the most promising eukaryotic H2 producers. In this model microorganism, light energy, H2 O and H2 are linked by two excellent catalysts, the photosystem 2 (PSII) and the [FeFe]-hydrogenase, in a pathway usually referred to as direct biophotolysis. This review summarizes the main advances made over the past decade as an outcome of the discovery of the sulfur-deprivation process. Both the scientific and technical barriers that need to be overcome before H2 photoproduction can be scaled up to an industrial level are examined. Actual and theoretical limits of the efficiency of the process are also discussed. Particular emphasis is placed on algal biohydrogen production outdoors, and guidelines for an optimal photobioreactor design are suggested.